Kualitas Warna dan Performa Benih Ikan Koi (Cyprinus carpio) yang Diberi Pakan Tepung Rebon dengan Penambahan Astaxanthin - Resiani, Resiani; Isriansyah, Isriansyah; Sukarti, Komsanah (Jurnal Pertanian Terpadu, 2022)
The purpose of this study was to analyze the effect of astaxanthin that added to rebon flour feed on the color quality and performance of koi fish fry and to determine the appropriate dose of astaxanthin addition to the feed. This experiment used a completely randomized design (CRD), consisted of four treatments and three replications. The treatments was the addition of astaxanthin in the rebon flour feed. Each treatments added astaxanthin 0%, 0.1%, 0.3%, 0.5%. Fish color in each treatment was observed using a modified Tocca Color Finder (TCF) and Adobe Photoshop software. The results of this study indicate that the addition of astaxanthin to the rebon flour feed gave a significantly different effect on to color level based on TCF and red color dimensions (P<0,05). However, there was not a significantly different on to survival rate and growth rate. The results of this study also showed that the addition of 0.1% astaxanthin gave the best color for koi fish fry.